Manifestations of grammatical interpretation in the Holy Quran: Surat Al-Shoura as an example - Almalahmeh, Mohammad Salem (Journal of Humanities & Social Sciences, 2020)
This paper studies the topic of grammatical interpretation in a descriptive and analytical study، applying to the linguistic phenomena that emerged from the grammatical interpretation of the verses of Surat Al-Shura from the Holy Qur’an. They are: deletion، rank، syntax، increase، load on meaning، and referral. Where grammatical interpretation is the tool of the Arab mind in understanding the grammatical phenomena that have been closed. Accordingly، the researcher’s department has this letter to an introduction، two papers، and a conclusion distributed as follows The first topic: Interpretation، its concept، causes، means، and its relationship to interpretation. The second topic: The applied part، Surat Al-Shoura. The phenomena dealt with in the term grammatical interpretation represent the main nerve of the textual cohesion argument in modern linguistics، and as a whole, they are the basic foundations for a study toward text. The added meanings of these phenomena have highlighted what we might call another text، which is the conscious image that highlights the fact that the great Qur’anic text is miraculous.